Solar energy resource assessment of the geba catchment, Northern Ethiopia - Mahmud, A.M. (Elsevier Ltd, 2014)
The global shift towards renewable energy is manifested in developing countries such as Ethiopia primarily because of continuous economic growth in the last two decades and secondly due to the vast untapped potential resources. In addition to other factors, the lack of accurate data of the resources has, however, hampered the development of solar energy technologies. The aim of this paper is to investigate the resource estimation by undertaking direct measurements at selected sites in the Northern part of Ethiopia. This paper presents an assessment of the solar energy resource based on the primary data collected between January 2011 and December 2012. The daily and monthly average global solar radiation is analyzed based on the 10 minute interval measurement retrieved from the data loggers. From the analysis it is seen that the measured values give a better accuracy and distribution of the global solar radiation than earlier Fig.s that were based on satellite images and model calculations. Furthermore, these results can be used to determine the solar resource potential of Northern Ethiopia for further energy development. Â© 2014 Published by Elsevier Ltd.